Analysis of Mutational Profile of Hypopharyngeal and Laryngeal Head and Neck Squamous Cell Carcinomas Identifies KMT2C as a Potential Tumor Suppressor - Machnicki, Marcin M.; Rzepakowska, Anna; Janowska, Joanna I.; Pepek, Monika; Krop, Alicja; Pruszczyk, Katarzyna; Stawinski, Piotr; Rydzanicz, Malgorzata; Grzybowski, Jakub; Gornicka, Barbara; Wnuk, Maciej; Ploski, Rafal; et al. (Frontiers in Oncology, 2022)
Hypopharyngeal cancer represents one of poorly characterized types of head and neck tumors with bleak prognosis and only few studies focusing specifically on the genomic profile of this type of cancer. We performed molecular profiling of 48 HPV-negative tumor samples including 23 originating from hypopharynx and 25 from larynx using targeted next-generation sequencing approach. Among genes previously described as significantly mutated, TP53, FAT1, NOTCH1, KMT2C and CDKN2A were found to be most frequently mutated. We also found that more than three-fourths of our patients harbored candidate actionable or prognostic alterations in genes belonging to RTK/ERK/PI3K, cell-cycle and DNA-damage repair pathways. Using previously published data we compared 67 hypopharyngeal cancers to 595 head and neck cancers from other sites and found no prominent differences in mutational frequency except for CASP8 and HRAS genes. Since we observed relatively frequent mutations of KTM2C (MLL3) in our dataset, we analyzed their role in vitro by generating KMT2C-mutant hypopharyngeal cancer cell line FaDu with CRISPR-Cas9. We demonstrate that KMT2C loss-of-function mutations result in increased colony formation and proliferation, in concordance with previously published results. In summary, our results show that mutational profile of hypopharyngeal cancers might be similar to the one observed for other head and neck cancers with respect to minor differences and includes multiple candidate actionable and prognostic genetic alterations. We also demonstrate for the first time that KMT2C gene may play a role of tumor suppressor in head and neck cancer, which opens new possibilities in the search for new targeted treatment approaches.